Breast Cancer Biology - Afroze, Dil; Rah, Bilal; Ali, Shazia; Shehjar, Faheem; Ishaq Dar, Mohd; Chauhan, Shailender S.; Thakur, Natasha (IntechOpen, 2020)
This book offers a comprehensive overview of recent developments in the field of breast cancer biology. It is a complete and descriptive reference on motioning pathways and new treatment options for the future transnational scientists and clinicians working on cancer research and treatment. We greatly appreciate the work of all the contributors to this book. They have brought with them tremendous diversity of perspectives and fields, which is truly reflective of the complexity of the topic, and they have come together in this project to serve as the node of multidisciplinary collaboration in this field. Finally, we must acknowledge the thousands of cancer patients who have participated in the studies, and who have inspired us to gather information to significantly progress knowledge in the field in recent years.